IMPROVING STUDENTS’ WRITING ACHIEVEMENT THROUGH LEARNING STYLES - Iwansyah Putra; Faoyan Agus Purwanto; Neneng Islamiah (Jurnal Penelitian)
Writing is an extremely complex cognitive activity in which the writer is required to demonstrate control of variables simultaneously. This research aimed to investigate whether there was a significant difference of students’ writing achievement before and after being taught through students’ learning style. Since the students of Islamic Senior High School in Sekayu still found it very difficult to do. The sample of the research was eleventh grade student. The research was conducted by applying quasi-experimental factorial research. Non-randomized sampling technique was applied in this research. Modality Test Questioners from Neil Fleming was applied to determine students’ learning styles. The sample was 62 students of science students. In terms of pretest – posttest non- equivalent group design. The Mean of posttest’s score was higher than pre-test. It means that there is an increase of students’ writing’s achievement after being taught through their styles in learning. Writing is an extremely complex cognitive activity in which the writer is required to demonstrate control of variables simultaneously. This research aimed to investigate whether there was a significant difference of students’ writing achievement before and after being taught through students’ learning style. Since the students of Islamic Senior High School in Sekayu still found it very difficult to do. The sample of the research was eleventh grade student. The research was conducted by applying quasi-experimental factorial research. Non-randomized sampling technique was applied in this research. Modality Test Questioners from Neil Fleming was applied to determine students’ learning styles. The sample was 62 students of science students. In terms of pretest – posttest non- equivalent group design. The Mean of posttest’s score was higher than pre-test. It means that there is an increase of students’ writing’s achievement after being taught through their styles in learning.